Cara membangun kepribadian dominasi rasional - Fajar Bilqis (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2019)
Conditioning feeling dominance is very high in Indonesia. This causes the level of community rationality, especially among adolescents has decreased. In fact, rationality is very important to make someone able to adjust to the environment. Therefore it is necessary to establish the personality of rational domination. Through this article, the study focuses on how to establish rational personalities. The formation of personality of rational dominance can be achieved by objective thinking, scientific thinking (following the problem solving procedure), providing reinforcement, and conditioning oneself to a rationally dominated environment. The formation of a rational personality will be beneficial to someone, that is, someone can judge whether an action is good or bad from the ability to consider, can overcome and regulate his emotional state, can easily deal with problems, can adjust to the environment, more independent without having to always depend on others to face difficulties, and can achieve life success.